PENGARUH KEGIATAN EKSTRAKURIKULER PIDATO TERHADAP MINAT DAN KEMAMPUAN LITERASI SISWA MINU UNGGULAN SUKOREJO - Midya Yuli Amreta; Miftakhul Rosyida; Af’idatur Rosyidah; Nisa’ul Khanifah; Hafni Zukhrufina; Shafira Aulia Agustin; Septia Relan Alivia Nanda Baisroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the influence of extracurricular speech activities on students' literacy interests and abilities at MINU Unggulan Sukorejo. Speech activities as part of non-formal learning are believed to be able to foster learning motivation, increase self-confidence, and encourage students to be more active in reading and writing. This study uses a qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The objects of the study consisted of students participating in the speech extracurricular, supervising teachers, and parents of students. The results of the study indicate that student involvement in speech activities can increase their interest in literacy activities, especially in the aspects of reading and compiling ideas in a structured manner. In addition, students also show development in speaking skills, critical thinking, and sensitivity to reading content. Therefore, extracurricular speech activities make a positive contribution to strengthening the culture of literacy in the MINU Unggulan Sukorejo environment.